Spatiotemporal Dynamics of Forest Carbon Sinks in China’s Qinba Mountains: Insights from Sun-Induced Chlorophyll Fluorescence Remote Sensing - Yuhang Lian; Yi He; Li Wang; Yaoting Wu; Yujie Wang; Zixuan Xu; Xinwen Xu; Lei Wang (Remote Sensing)
Forest carbon sinks are crucial in mitigating climate change as integral components of the global carbon cycle. Accurately estimating forest carbon sinks using traditional remote sensing indices, such as Normalized Difference Vegetation Index(NDVI), presents significant challenges, particularly in complex terrains and regions with variable climates. These limitations hinder the effective capture of photosynthetic dynamics. To address this gap, this study leverages Sun-Induced Chlorophyll Fluorescence (SIF) remote sensing, highlighting its superiority over traditional indices in capturing photosynthetic processes and offering a more precise approach to estimating carbon sinks in climate-sensitive mountainous areas. Using SIF data from GOSIF, alongside models for light-use efficiency and ecosystem respiration, this study estimates forest carbon sinks in the Qinba Mountains of China during the growing season (June to September) from 2011 to 2018. The results are further validated and analyzed in terms of forest age and type. Key findings include: (1) The average annual forest carbon sinks during the growing season was approximately 24.51 TgC; (2) Spatially, higher carbon sinks values (average 36.79 gC·m⁻2·month⁻1) were concentrated in the western and central Qinba areas, while southeastern and central-northern regions exhibited lower values (average 7.75 gC·m⁻2·month⁻1); (3) Temporally, minimal interannual variation was observed in the northwest, whereas the southeast showed fluctuating trends, with an initial decline followed by an increase; (4) Forest carbon sinks was significantly influenced by forest age, type, and altitude. Our findings demonstrate that plantation forests aged 10 to 30 years exhibit superior carbon sequestration capacity compared to natural forests, while natural forests aged 70 to 90 years also show significant carbon sinks potential. These results underscore the crucial influence of forest characteristics on carbon sequestration dynamics. By examining these spatiotemporal patterns in the Qinba Mountains, our study offers valuable insights for advancing China’s ‘dual carbon’ goals, emphasizing the importance of strategic forest management in mitigating climate change.